Penerapan cognitive behavior therapy (CBT) untuk meningkatkan motivasi belajar mahasiswa psikologi pasca-liburan semester - Itsni Handika Azzahara; Anniez Rachmawati Musslifah (Fukuri: Journal of Psychology, 2025)
Abstract Decreased motivation to study after a holiday is a common phenomenon experienced by students, especially due to the influence of internal factors such as negative thoughts and external factors such as technological distractions and social isolation. This study aims to explore the application of Cognitive Behavior Therapy (CBT) in overcoming decreased motivation to study in psychology students. The approach used is descriptive qualitative with a subject of a 21-year-old female student who showed symptoms of procrastination and difficulty focusing after a semester break. Data were collected through interviews, observations, and counseling notes. Interventions were carried out through three main CBT techniques: cognitive restructuring, behavioral activation, and goal setting. The results showed an increase in self-awareness, changes in negative thought patterns, and the formation of healthier study routines. These findings indicate that CBT is effective as a psychological intervention strategy to restore and improve students' motivation to study during the academic transition period.   Penurunan motivasi belajar pasca-liburan merupakan fenomena umum yang dialami oleh mahasiswa, terutama akibat pengaruh faktor internal seperti pikiran negatif dan faktor eksternal seperti distraksi teknologi serta isolasi sosial. Penelitian ini bertujuan untuk mengeksplorasi penerapan Cognitive Behavior Therapy (CBT) dalam mengatasi penurunan motivasi belajar pada mahasiswa psikologi. Pendekatan yang digunakan adalah deskriptif kualitatif dengan subjek seorang mahasiswi berusia 21 tahun yang menunjukkan gejala prokrastinasi dan kesulitan fokus setelah liburan semester. Data dikumpulkan melalui wawancara, observasi, dan catatan konseling. Intervensi dilakukan melalui tiga teknik CBT utama: restrukturisasi kognitif, aktivasi perilaku, dan penetapan tujuan. Hasil menunjukkan adanya peningkatan kesadaran diri, perubahan pola pikir negatif, serta terbentuknya rutinitas belajar yang lebih sehat. Temuan ini menunjukkan bahwa CBT efektif sebagai strategi intervensi psikologis untuk mengembalikan dan meningkatkan motivasi belajar mahasiswa di masa transisi akademik.